Anti-Glycan Autoantibodies Induced by Helicobacter pylori as a Potential Risk Factor for Myocardial Infarction - Negrini, Riccardo; Villanacci, Vincenzo; Poiesi, Claudio; Savio, Antonella (Frontiers in Immunology, 2020)
A number of epidemiological studies have evaluated the potential association between H. pylori and cardiovascular disease, but with contrasting results. We have previously shown that Helicobacter pylori infection is able to induce in mice and humans autoantibodies cross-reacting with histo–blood group Lewis antigens, expressed in different organs and in plasma glycoproteins and glycolipids. The aim of this study was to assess whether immunization of animals with H. pylori might induce myocardial histopathological changes. We have retrospectively examined, in detail, the histology of archived organs from mice and rabbits immunized with H. pylori in our previous studies. Human sera and cross-reacting monoclonal antibodies were also tested against bacterial preparations and tissue sections. Areas of myocardial necrosis, associated with coronary thrombotic occlusion, were found in 5 of 20 mice and 2 of 5 rabbits previously immunized with suspensions of H. pylori. No similar lesions were found in control animals, suggesting a causal link with H.pylori immunization. The animals bearing myocardial lesions had not been infected but only immunized months earlier with parenteral injections of dead H. pylori cells. This strongly suggests that immunization, by itself, might play a causative role. We propose that the cross-reactive autoimmune response induced by H. pylori could promote thrombotic occlusion through direct endothelial damage or by perturbing the coagulation process.